Association of halitosis with dental caries in pediatric patients in a tertiary level hospital (Bangabandhu Sheikh Mujib Medical University Journal, 2022)
Halitosis refers to bad breath is induced by volatile molecules due to pathological or non-pathological factors, prevalent in all ages. It can originate from either oral or non-oral sources. However, dental hygiene, periodontal disease, impacted food, tongue coat, and caries are among the oral-related sources, accounting for 90% of cases of halitosis. Therefore, this study aimed to evaluate the association between halitosis and caries among pediatric patients. This cross-sectional descriptive study documented clinical data from 45 pediatric patients at Bangabandhu Sheikh Mujib Medical University (BSMMU). The selected patients were evaluated with the Specific Caries Index (SCI) to detect the caries involvement. A halimeter was used to evaluate halitosis. According to halimeter, the mean value of halitosis in relation to sex was 169.58 ppb, while participants with very strong halitosis were observed in 12.5% of males and 33.3% of females. Patients over the age of 13 manifested extreme halitosis than other selected age groups. The result demonstrated that halitosis increased significantly with a higher score of the caries index. Hence, this study indicated an association between halitosis and the caries index in pediatric patients, highlighting the need for more research to assess its applicability in broader and diverse groupsBSMMU J 2021; 14(3): 62-66